A single center experience: physician related diagnostic delay and demographic and clinical differences between patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis - Ulutaş Firdevs; Çobankara Veli; Şenol Hande; Karasu Uğur; Kaymaz Serdar; Yaşar Canan Albayrak; Ök Zeynep Dündar; Yiğit Murat (Sciendo, 2021)
Background. A large number of comparative studies have been conducted for ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA), including disease burden, treatment modalities and patient characteristics. The aim of this study was to compare physician related diagnostic delay time between patients with AS and nr-axSpA.